Platinum(iv) dihydroxido diazido N-(heterocyclic)imine complexes are potently photocytotoxic when irradiated with visible light - Shaili, E; Salassa, L; Woods, JA; Clarkson, G; Sadler, PJ; Farrer, NJ (Royal Society of Chemistry, 2019)
A series of trans-di-(N-heterocyclic)imine dihydroxido diazido PtIV complexes of the form trans,trans,trans-[Pt(N3)2(OH)2(L1)(L2)] where L = pyridine, 2-picoline, 3-picoline, 4-picoline, thiazole and 1-methylimidazole have been synthesised and characterised, and their photochemical and photobiological activity evaluated. Notably, complexes 19 (L1 = py, L2 = 3-pic) and 26 (L1 = L2 = 4-pic) were potently phototoxic following irradiation with visible light (420 nm), with IC50 values of 4.0 μM and 2.1 μM respectively (A2780 cancer cell line), demonstrating greater potency than the previously reported complex 1 (L1 = L2 = py; 6.7 μM); whilst also being minimally toxic in the absence of irradiation. Complexes with mixed N-(heterocyclic)imine ligands 19 and 20 (L1 = py, L2 = 4-pic) were particularly photocytotoxic towards cisplatin resistant (A2780cis) cell lines. Complex 18 (L1 = py, L2 = 2-pic) was comparatively less photocytotoxic (IC50 value 14.5 μM) than the other complexes, despite demonstrating the greatest absorbance at the irradiation wavelength and the fastest half-life for loss of the N3 → Pt LMCT transition upon irradiation (λirr = 463 nm) in aqueous solution. Complex 29 (X1 = X2 = thiazole) although potently phototoxic (2.4 μM), was also toxic towards cells in the absence of irradiation.